Multi-level analysis of nutrient cycling within agro-sylvo-pastoral landscapes in West Africa using an agent-based model. (September 2018) - Grillot, Myriam; Guerrin, François; Gaudou, Benoit; Masse, Dominique; Vayssières, Jonathan
Abstract: Livestock-driven nutrient flows are the main sources of soil and crop fertilization in West African agro-sylvo-pastoral landscapes. They result from nutrient recycling between farm activities and the spatial transfer of nutrients within the landscape. "Extensive" systems, based on livestock mobility are tending to be replaced by more "intensive" systems based on in-barn livestock fattening. We built an agent-based model to compare these systems in terms of nitrogen cycling at land plot, herd, household and village levels. Model evaluation, based on field-data from two real contrasted villages, showed that the model satisfactorily reproduces the differences between an "extensive" and an "intensive" system with key parameters such as variability among households and soil fertility gradients. Simulations highlighted bottlenecks along the nitrogen (N) cycle like accumulation of N in manure heaps and housing areas, reducing N recycling efficiency, especially in "intensive" systems. The model can be further used to explore improved agro-sylvo-pastoral landscapes. Graphical abstract: Image 1 Highlights: The TERROIR agent-based model represents the nitrogen (N) cycle within agro-sylvo-pastoral landscapes. Two conceptual stock-flow models are interlinked to represent N recycling and spatial transfers. N flows differ from one household to another according to their resource endowment and management decisions. The model enables detailed multi-level analysis of the N cycle from few input data collected at landscape level.